2011
DOI: 10.1088/0953-4075/44/13/135503
|View full text |Cite
|
Sign up to set email alerts
|

Generation of superposition states and charge-qubit relaxation probing in a circuit

Abstract: We demonstrate how a superposition of coherent states can be generated for a microwave field inside a coplanar transmission line coupled to a single superconducting charge qubit, with the addition of a single classical magnetic pulse for chirping of the qubit transition frequency. We show how the qubit dephasing induces decoherence on the field superposition state, and how it can be probed by the qubit charge detection. The character of the charge qubit relaxation process itself is imprinted in the field state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…Specifically, we focused on fullerene molecules and observed that when the time scales of decoherence and dissipation are close and dependent on the propagation time during which the system is coupled to the environment, the inclusion of dissipation becomes necessary. The combined effect of decoherence and dissipation leads to a more significant degradation of quantum behavior compared to pure decoherence, providing further insights for understanding other systems [14,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we focused on fullerene molecules and observed that when the time scales of decoherence and dissipation are close and dependent on the propagation time during which the system is coupled to the environment, the inclusion of dissipation becomes necessary. The combined effect of decoherence and dissipation leads to a more significant degradation of quantum behavior compared to pure decoherence, providing further insights for understanding other systems [14,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The more relevant dissipative effect comes in fact from the superconducting charge qubit decayng time [39] (see [5] for a compreensive review of some recent experimental numbers). At the frequencies of GHz necessary for the present porposal the charge qubit decay will affect the squeezing of the TLR 2 field, and therefore will affect the accuracy of the detection process.…”
Section: Discussionmentioning
confidence: 99%
“…Those states have been historically proved to be hard to generate [4,24], but in principle they could be easily engineered in microwave fields in coplanar transmission lines, as has been demonstrated recently [25]. Previously, in [16] we demonstrated an alternative proposal to generate a superposition of coherent states of a microwave field in a transmission line resonator through interaction with a single superconducting charge qubit controlled by an external single classical magnetic pulse. By assuming a continuously varying magnetic pulse the generation can almost be deterministic.…”
Section: Introductionmentioning
confidence: 94%
“…For a 'fast' pulse x (t ) (a pulse with a duration equal or shorter than the half-period of oscillations) (see [16]), and when the 'artificial atom' and central line resonator field are prepared in an initial state |0 |α at t 0 = 0, the first-order terms in equation ( 6) are negligible and we can consider only terms of second order. So the temporal evolution…”
Section: Time-dependent State Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation